Cassini plasma observations of Saturn's magnetospheric cusp. Issue 12 (30th December 2016) - Jasinski, Jamie M.; Arridge, Christopher S.; Coates, Andrew J.; Jones, Geraint H.; Sergis, Nick; Thomsen, Michelle F.; Reisenfeld, Daniel B.; Krupp, Norbert; Waite, J. Hunter
Abstract: The magnetospheric cusp is a funnel‐shaped region where shocked solar wind plasma is able to enter the high‐latitude magnetosphere via the process of magnetic reconnection. The plasma observations include various cusp signatures such as ion energy dispersions and diamagnetic effects. We present an overview analysis of cusp plasma observations at the Saturnian magnetosphere from the Cassini spacecraft era. A comparison of the observations is made as well as classification into groups due to varying characteristics. The locations of the reconnection site are calculated and shown to vary along the subsolar magnetopause. We show the first in situ evidence for lobe reconnection that occurred at nearly the same time as dayside reconnection for one of the cusp crossings. Evidence for "bursty" and more "continuous" reconnection signatures is observed at different cusp events. The events are compared to solar wind propagation models, and it is shown that magnetic reconnection and plasma injection into the cusp can occur for a variety of upstream conditions. These are important results because they show that Saturn's magnetospheric interaction with the solar wind and the resulting cusp signatures are dynamic and that plasma injection in the cusp occurs due to a variety of solar wind conditions. Furthermore, reconnection can proceed at a variety of locations along the magnetopause. Key Points: Evidence for lobe and dayside magnetic reconnection occurring at times near simultaneously at Saturn Plasma signatures show that magnetic reconnection can occur in a "bursty" and "quiescent" manner Cusp observations occur for a variety of solar wind conditions